Managing water productivity, groundwater stress, and nexus trade-offs in the Ganga River Basin, India - Amarasinghe, Upali A.; Perera, Madhusha; Sikka, Alok; Mahapatra, Smaranika; Sarangi, A. (International Water Management Institute, 2025)
The Ganga River Basin (GRB) is a critical hotspot of the water-food-energy-environment (WFEE) nexus in South Asia, with severe pressures from groundwater over-extraction. Currently, 81 districts face overexploitation, where groundwater consumptive water use (GWCWU) exceeds 90% of extractable resources. Furthermore, 10 more districts are overexploited, 19 are critical, and 20 semi-critical, while 107 riparian districts still remain within safe limits.